(untitled) - Stott, John R. W. (England, 2003)
Why Jesus? Perhaps you're intrigued with what you have heard about Jesus Christ. Or you might have had the funny feeling that God wants to get your attention. Or maybe you're simply looking for meaning and direction in your life. John Stott has spent a lifetime wrestling with questions about Jesus both personally and in dialogue with skeptics and seekers around the globe. Now in Why I Am a Christian he provides a compelling, persuasive case for considering the Christian faith. If we take an honest look at Jesus, we will discover that following him gives us the purpose, identity and freedom we've been searching for--and far more than we had ever imagined.
Keywords: Doctrinal theology